Prospective study reveals a microbiome signature that predicts the occurrence of post-operative enterocolitis in Hirschsprung disease (HSCR) patients. (3rd July 2020) - Tang, Weibing; Su, Yang; Yuan, Chen; Zhang, Yuqing; Zhou, Lingling; Peng, Lei; Wang, Pin; Chen, Guanglin; Li, Yang; Li, Hongxing; Zhi, Zhengke; Chang, Hang; et al.
ABSTRACT: Hirschsprung disease (HSCR) is a birth defect with an approximate incidence of 1/5, 000 live births, and up to one-third of HSCR patients develop Hirschsprung-associated enterocolitis (HAEC), the leading cause of HSCR-related death. Very little is known about the pathogenesis, prevention, and early diagnosis of HAEC. Here, we used a prospective study to investigate the enteric microbiome composition at the time of surgery as a predictor for developing postoperative HAEC. We identified a microbiome signature containing 21 operational taxonomic units (OTUs) that can potentially predict postoperative HAEC with ~85% accuracy. Furthermore, we identified exclusive breastfeeding as a novel protective factor for total HAEC (i.e., preoperative and postoperative HAEC combined). In addition, we discovered that breastfeeding was associated with a lowered risk for HAEC potentially mediated by modulating the gut microbiome composition characterized by a lower abundance of Gram-negative bacteria and lower LPS concentrations. In conclusion, modulating the gut microbiome by encouraging breastfeeding might prevent HAEC progression in HSCR patients.